2,4,6-Trichloroanisole: A consumer panel evaluation - Teixeira,Margarida I. V. (2006)
The "cork taint" is a major problem in wine industry and may caused by the several sources of contamination although wine cork stoppers are usually subject to suspition: 2,4,6-trichloroanisole (TCA) has been frequently associated to this off-flavour. In this work, a consumer panel performed "forced choice" triangular tests in order to measure Odour Detection Thresholds (ODT) and Taste Detection Thresholds (TDT) of TCA in water, hydro-alcoholic solutions (11.5% and 18% ethanol) and white and red wines. A paired preference test was also performed by the panel in order to measure Odour Rejection Threshold (ORT) in white and red wines spiked with TCA. Results obtained show that the ODT and the TDT for TCA were respectively: 0.2 and 0.3 ng/ L in water, 0.9 and 1.7 ng/L in red wine and 1.5 and 1.0 ng/L in white wine. ODT were 4 and 10 ng/L respectively for hydro-alcoholic solutions with 11.5% and 18% ethanol. ORT for white wines was 10.4 ng/L and for red wines 16.0 ng/L. These results suggest that although this group of non trained assessors detected very low concentrations of TCA in wines, they did not reject the wine at these low concentration values.